(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article, the problem of interconfessional relations is considered, which is one of the most urgent today. There have been attempts to politicize confessional organizations, which can also become a factor in exacerbating inter-confessional relations. In the conditions of the transitional period, which our society is now experiencing, the construction and development of constructive interfaith relations that can influence the strengthening of the processes of social stabilization and integration of the Kazakh state are of great importance. The change in the state structure of Kazakhstan requires new approaches in the state policy towards religious organizations that take into account the multifaceted nature of this problem. One of such approaches can be the shift of the accents of interconfessional relations from the doctrinal plane to the level of culture, which will help to smooth existing contradictions. Key words: Religion, tolerance, globalization, confession, religious worldview.